Extended FDD-WT method based on correcting the errors due to non-synchronous sensing of sensors. (May 2016) - Tarinejad, Reza; Damadipour, Majid
Abstract: In this research, a combinational non-parametric method called frequency domain decomposition-wavelet transform (FDD-WT) that was recently presented by the authors, is extended for correction of the errors resulting from asynchronous sensing of sensors, in order to extend the application of the algorithm for different kinds of structures, especially for huge structures. Therefore, the analysis process is based on time-frequency domain decomposition and is performed with emphasis on correcting time delays between sensors. Time delay estimation (TDE) methods are investigated for their efficiency and accuracy for noisy environmental records and the Phase Transform – β (PHAT-β) technique was selected as an appropriate method to modify the operation of traditional FDD-WT in order to achieve the exact results. In this paper, a theoretical example (3DOF system) has been provided in order to indicate the non-synchronous sensing effects of the sensors on the modal parameters; moreover, the Pacoima dam subjected to 13 Jan 2001 earthquake excitation was selected as a case study. The modal parameters of the dam obtained from the extended FDD-WT method were compared with the output of the classical signal processing method, which is referred to as 4-Spectral method, as well as other literatures relating to the dynamic characteristics of Pacoima dam. The results comparison indicates that values are correct and reliable. Highlights: An approach, FDD-WT, is introduced to estimate the modal parameters of infrastructures. The effects of non-synchronous sensing of sensors are considered in new approach. An efficient and accurate time delay estimation method is selected and applied. A theoretical example (3DOF system) is presented to indicate the efficiency and accuracy. Modal properties of the Pacoima dam is re-identified and discussed.